Peningkatan Literasi Digital bagi Mahasiswa Kesehatan Universitas Jenderal Achmad Yani Yogyakarta melalui Sosialisasi: Digital Literacy Improvement for Health Students at Universitas Jenderal Achmad Yani Yogyakarta Through Socialization - Purwanti, Endang; Nugroho, Dwi; Sari, Rizky Yuspita; Raharjo, Untoro Dwi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Healthcare services are advancing with the development of information and communication technology. Basic literacy is crucial for improving healthcare efficiency and quality. In Indonesia, the implementation of basic literacy faces challenges such as the readiness of healthcare professionals, students' lack of understanding, and resistance to change. Therefore, Universitas Jenderal Achmad Yani Yogyakarta (Unjaya) must organize basic literacy socialization activities for healthcare students. These activities aim to introduce basic literacy concepts, enhance students' understanding of its benefits and technical implementation, and address obstacles like technological ignorance and resistance to change. Through an interactive and practical approach, students are expected to acquire the necessary understanding and skills for future clinical practice. Twenty-two students from the Nursing, Blood Bank Technology, Pharmacy, and Midwifery programs will participate. Educational videos will be used for socialization, followed by pretests and post-tests to evaluate understanding. Evaluation results show increased knowledge before and after the socialization.